The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1111/j.1748-0361.2011.00370.x
|View full text |Cite
|
Sign up to set email alerts
|

The Adoption and Use of Health Information Technology in Rural Areas: Results of a National Survey

Abstract: HIT adoption and use in rural primary care offices does not appear to be lower than in urban offices. The situation, however, is dynamic and warrants further monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 30 publications
(45 reference statements)
1
56
0
Order By: Relevance
“…Although previous analysis of national survey data by Singh et al showed that practices in rural areas actually had 3.7 times higher rates of adoption than those in urban areas, our data suggest that RHCs have a uniquely higher chance of not adopting EHR, and may be different in this respect from other practices in rural areas. 15 …”
Section: Discussionmentioning
confidence: 99%
“…Although previous analysis of national survey data by Singh et al showed that practices in rural areas actually had 3.7 times higher rates of adoption than those in urban areas, our data suggest that RHCs have a uniquely higher chance of not adopting EHR, and may be different in this respect from other practices in rural areas. 15 …”
Section: Discussionmentioning
confidence: 99%
“…1001 completed surveys were received during this process. The survey and data collection are described in more detail in Singh et al [20]. Because this current study investigates the impact of actual EMR usage on health care outcomes, our data analysis only includes the physician offices which had already adopted EMR systems and whose data are complete for all variables included in our model, which lead to 222 observations in our final analysis.…”
Section: Methods Datamentioning
confidence: 99%
“…One advantage of this style of interaction is that it may be more efficient, in terms of time spent interacting with the patient and inputting necessary data during the visit, which leads to minimal time spent charting after the visits. However, physicians who rely on this interaction style may experience challenges in situations where it may be necessary to provide care without technologies (Singh et al, 2012). Other disadvantages are that this group may not be able to communicate empathy appropriately when it is necessary because of the methods they tend to use (multitasking with short verbal and nonverbal interactions).…”
Section: Discussionmentioning
confidence: 99%